Future Well-Being Among People Who Attempt Suicide and Survive: Research Recommendations. Issue 5 (September 2021) - Tong, Bingjie; Kashdan, Todd B.; Joiner, Thomas; Rottenberg, Jonathan
Highlights: Attempted suicide is associated with many negative outcomes. Little is known about more favorable outcomes after nonfatal suicide attempts. Research recommendations are provided for examining well-being among suicide attempt survivors. Abstract: Over 48, 000 people died by suicide in 2018 in the United States, and more than 25 times that number attempted suicide. Research on suicide has focused much more on risk factors and adverse outcomes than on protective factors and more healthy functioning. Consequently, little is known regarding relatively positive long-term psychological adaptation among people who attempt suicide and survive. We recommend inquiry into the phenomenon of long-term well-being after nonfatal suicide attempts, and we explain how this inquiry complements traditional risk research by (a) providing a more comprehensive understanding of the sequelae of suicide attempts, (b) identifying protective factors for potential use in interventions and prevention, and (c) contributing to knowledge and public education that reduce the stigma associated with suicide-related behaviors.